A Historical Exploration of Auditing Practices and Principles - Muslim, Muslim (Advances in Managerial Auditing Research, 2024)
The purpose of this research is to explore the historical evolution of auditing practices and principles, examining the influences of economic, technological, and regulatory factors. A comprehensive review of literature spanning ancient civilizations to modern-day developments provides insights into the dynamic nature of auditing over time. The research design and methodology involve a systematic analysis of scholarly articles, historical texts, and regulatory documents to trace the evolution of auditing from its rudimentary origins to its contemporary multidimensional framework. Findings reveal significant milestones, including the establishment of professional accounting bodies, regulatory reforms such as the Sarbanes-Oxley Act, and technological innovations like data analytics and blockchain technology, which have shaped auditing standards and practices. The discussion delves into the implications of these findings, emphasizing the need for continued research and interdisciplinary collaboration to address emerging challenges and stakeholder expectations. The implications of this research extend to academia, practice, and policy, highlighting the importance of understanding auditing's historical context in informing decision-making, policy development, and professional development initiatives.